PENGARUH MEDIA REALITA PADA PEMBELAJARAN MATEMATIKA TERHADAP HASIL BELAJAR SISWA KELAS III SEKOLAH DASAR - Kurniawan Nur Akbari; Margiati Margiati; Tahmid Sabri (Universitas Tanjungpura, 2019)
AbstractThis research was aimed to find out whether there was a significant difference between the average of students’ result in learning mathematics by using realia media (stick and pouch of numbers). The method used in this research was experimental and the form of research was Pre-Experimental Design. The research population was all students of grade III A in Sekolah Dasar Negeri 16 Pontianak Selatan. The sample was class III A (experimental class) conswasts of 32 students. Data collecting method used was measurement technique and the tool used was written test in form of essay. The result of experimental class average pre-test score was 62,25 and for the post-test of experimental class 2 was 78,75. Based on the calculation above, the result of t count was 15,76 with db=32-1=31 with significance rate (a) = 5% resulted in t table 1,670. Based on t count result in 15,76> t table 1,670, it can be concluded that Ha was accepted. It means there was a difference in students’ learning result before and after the treatment of Realia. Thus, it can be concluded the implementation of Realia Media does affects in the students’ learning result in mathematics in class III A of Sekolah Dasar Negeri 16 Pontianak Selatan. Key words : The influence of reality media, the results of the mathematics study